A cross-sectional study of relationship between self-esteem and self-concept of students of medical sciences - Amirkhani, Mehdi; Habibi, Fatemeh; Hakimi, Azadeh; Najafi Kalyani, Majid; Salami, Javad (International Journal of Research in Medical Sciences, 2018)
Background: Identification of the role of factors such as self-esteem and self-efficacy and the investigation of their relationship among students can bring about improvement of educational planning and enhance the teaching outcome. This study aimed at investigating the relationship between self-esteem and self-efficacy among the students of medical sciences. Methods: The present study is an analytical-descriptive which was conducted as a cross-sectional study on 394 students of Fasa University of Medical Sciences in 2016. In order to collect the data two questionnaires were used namely, Coopersmith Self-Esteem Inventory (CSEI) and Rogers Self-concept Questionnaire. The data were analyzed using SPSS 22. The researchers used descriptive and inferential statistics such as t-test, chi-square one-way ANOVA, and correlation to analyze the data. Results: The mean and the standard deviation of self-esteem scores of female and male students were 38.23±6.80 and 37.51±6.67 respectively. The mean and the standard deviation of self-concept scores of female and male students were 9.49±3.53 and 9.43±4.14 respectively. The mean of self-concept scores of students of different majors had statistically significant difference with each other (0.011), whereas there was no statistically significant difference in self-esteem scores among students with different majors (0.442). Conclusions: Considering the statistically significant difference in students’ self-concept scores in different majors, it is suggested that we take right approaches to the improvement and enhancement of individuals’ self-concept and the creation of positive feedback.